The quality of research in sports journals. Issue 2 (1st April 2002) - Bleakley, C; MacAuley, D
Abstract : Objective: To examine the evidence base of sports medicine research. Methods: A sample of four major journals that present core research in sport and exercise medicine ( British Journal of Sports Medicine, Medicine and Science in Sports and Exercise, Journal of Sports Medicine and Physical Fitness, and Physical Therapy ) was examined using assessment criteria taken from the READER method. Results: Randomised controlled trials comprised 10% or less of all original research articles. Observational/descriptive studies were the most commonly published study design. There was a highly significant difference (p<0.0001) in the contents of the four journals but when they were compared by categorising the better quality methods together (randomised control trial, case-control, and cohort studies), the difference was not significant (p = 0.09). Conclusions: The overall pattern of publication type seems remarkably stable over medical journals, indicating that the quality of sports medicine research is comparable to that in other specialities.